(NnAU^NYE ^TENIQ PAMQTI a(B.(Ni(B.(NkANDINSKOGOs (NMATERIALY NAU^(B.(NKONF(B.s - (Ne(B.(Ng(B.(NsOROKINAs (NRED(B.-(NSOST(B.s; (Ni(B.(Na(B.(NsKWORCOWAs ((NmOSKWAs (NmOSK(B.(NGOS(B.(NKONS(B.(NIM(B.(Np(B.(Ni(B.(N~AJKOWSKOGOs, 2007)
(NsBORNIK SODERVIT MATERIALY nAU^NYH ^TENIJ PAMQTI a(B.(Ni(B.(NkANDINSKOGO (B.s
Keywords: (NMONOGRAFIQs